Ecological and health risk assessment of polycyclic aromatic hydrocarbons (PAHs) in Sungai Perak, Malaysia - Abd Manan T.S.B.; Khan T.; Wan Mohtar W.H.M.; Beddu S.; Qazi S.; Sheikh Khozani Z.; Mohd Kamal N.L.; Sarwono A.; Jusoh H.; Yavari S.; Mustafa S.F.Z.; Hanafiah Z.; et al. (Elsevier Ltd, 2023)
Polycyclic aromatic hydrocarbons (PAHs) are mutagenic and bio-accumulates in nature. This research aims to determine the ecological and health risk assessment of PAHs in Sungai Perak, Malaysia. The sampling was conducted at the up and downstream of Sungai Perak in the district of Perak Tengah, Malaysia. The sampling stations were Tanjung Belanja Bridge (TBB), Water Treatment Plant Parit (WTPP), Parit Town Discharge (PTD), Water Treatment Plant Senin (WTPS) and Water Treatment Plant Kepayang (WTPK). The water treatment plants channel water through the distribution network, to Manjung (249,600 people), Perak Tengah (249,600 people), Kinta (810,400 people) and Hilir Perak (144,400 people) districts. The hazard quotient (HQ) and hazard index (HI) were applied for ecological and health risk assessments. The lifetime cancer risk (LCR) was employed for the health risk assessment. The PAHs contamination level presumptions for all sampling campaigns were low (0100 ?g/L). The HI values of ecological and health risk assessments were found to be aligned with each other. The HI values for raw water were below one (<1) indicating low or no risk while the treated water HI values were more than one (>1) indicating to high risk to aquatic organisms and human health. However, the LCR for raw and treated water exceeded the maximum permissible limit, 1.0 10?6 equals to cancer risk of 1 in 1,000,000 people. The LCR for raw water were 1.71 10?4 (TBB), 1.35 10?4 (WTPP), 1.43 10?4 (PTD), 9.54 10?5 (WTPS) and 2.37 10?4 (WTPK). Meanwhile, the LCR for treated water were 6.90 10?5 (WTPP), 5.42 10?5 (WTPS) and 2.63 10?4 (WTPK). The conventional water treatment system appears to be inefficient to remove PAHs, risking the security of public health. Thus, restructuring the infrastructure of water treatment plants or considering an alternative to rivers as domestic water sources are highly recommended. 2021 Elsevier Ltd